(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the relapse rate within 12 months and identify related factors in pediatric patients with Basedow disease at Children’s Hospital 2. Subjects and methods: A retrospective, descriptive case- series study was conducted on 34 pediatric patients who discontinued antithyroid therapy Methimazole (MMI) after completing treatment and were followed for at least 12 months or until relapse. Results: The relapse rate was 38.2% within one year after stopping MMI therapy. Factors associated with relapse included delayed diagnosis, which increased the risk of relapse, and longer durations of MMI treatment, which reduced the relapse rate. Conclusion: The relapse rate within 12 months is relatively common in pediatric Basedow patients. Extending the duration of MMI therapy to at least 18 months is essential to minimize the risk of relapse in children with Basedow disease.